Strategic Planning of Regional Oil and Fat Subcomplex of Russia - SINEGOVSKY, Mikhail O.; MALASHONOK, Anastasia A. (Journal of Advanced Research in Law and Economics, 2019)
The purpose of the given work is to analyze the trends in the development of the oil and fat subcomplex as one of the most important components of the agro-industrial complex of the Russian Federation, as well as state policy in the strategic planning in this sphere. The materials of the United States Department of Agriculture, the State Statistics Service and the Ministry of Agriculture of the Russian Federation served as an information basis for the research. Legislative and regulatory acts of the Russian Federation were used for the analysis of state policy in the field of strategic planning in the agro-industrial complex. The results of research showed that the development of the oil and fat subcomplex is hampered by a large number of problems, one of which is the absence of the target program-strategy of the development. The most optimal of the possible options for the development strategy is the formation of a cluster, that will allow optimizing the work of all its participants, involved in various spheres of the agro-industrial complex, logistic infrastructure, public authorities, scientific and personnel support, as well as contributes to solving the identified problems. In the study within the framework of the analysis of the internal and external environment of the oil and fat subcomplex, the problems that hamper its development are considered by the example of the All-Russian leader in the soybean production. The advisability of developing a state program for creating a cluster has been revealed and directions for implementing state support for solving technical and technological as well as social and economic problems have been determined.